The "Fram" expedition. Nansen in the frozen world. Preceded by a biography of the great explorer and copious extracts from Nansen's "First crossing of Greenland," also an account by Eivind Astrup, of life among people near the Pole, and his journey across northern Greenland with Lieut. R. E. Peary, U.S.N. Arranged and ed. by S. L. Berens . Followed by a brief history of the principal earlier Arctic explorations from the ninth century to the Peary expedition . by John E. Read . - Berens, S. L. (Philadelphia, Pa., A.J. Holman & co., 1897)
1 p. l., viii, [9]-560 p.